SAT0435 Tibial Spine Morphology and Association with Anterior Cruciate Ligament Degeneration – A Combined MRI, X-rays and Histology Study of Early Knee Osteoarthritis. (15th July 2016) - Tan, A.L.; Baboolal, T.; Benjamin, M.; Yonenaga, T.; Binks, D.; McGonagle, D.
Abstract : Background: Knee osteoarthritis (OA) may supervene on traumatic anterior cruciate ligament (ACL) injury/rupture. However, knee OA with advanced disease on MRI may have ACL deficiency without a history of injury. We hypothesised that the complex enthesis organ structure of the ACL with the adjacent tibial tuberosities might be predisposed to ACL degeneration, and hence the elaborate ACL enthesis organ might contribute to joint degeneration. Objectives: To describe the histology of the ACL enthesis organ structure including the relationship with the adjacent tibial spines and to determine whether tibial spine morphology and height (as determined by X-ray) may be linked to knee damage in early OA (as determined by MRI). Methods: 333 datasets from the progression cohort of the Osteoarthritis Initiative (OAI) with Kellgren and Lawrence (KL) scores ≤1 were analysed. The lateral and medial tibial spine heights (LH, MH) were measured perpendicular to the tibial plateau width (W) (figure ). 252 datasets with available corresponding MRI at 48 months were analysed for ACL injury and degeneration. Microanatomy of tibial spine was described from histology of tibial plateaus obtained from total knee replacement surgery. Results: 170 ACLs assessed at 48 months were scored as normal (67.5%). 73 (29%) had tibial side ACL degeneration; 1 (0.4%) had femoral side degeneration; 3 (1.2%) were completely degenerate, and 5 (2%) had a chronic ACL tear. A significant association was seen between the increasing mediolateral width of the tibial plateau and ACL degeneration (p<0.001). Significant associations were also observed between the medial tibial spine height and ACL degeneration (p=0.007); and between lateral tibial spine height and ACL degeneration; (p=0.009). No significant associations were observed when medial and lateral tibial spine heights were normalised to the tibial plateau width (i.e. MH/W, LH/W). Histology shows the ACL curves reciprocally around the spine and the adjacent surface is modified as a sesamoid fibrocartilage. The ligament shows evidence of degenerative changes (numerous small cysts and loss of normal fibrillar density). The cartilage covering the spine including the intercondylar notch area showed typical early OA changes (cell clustering, fissuring, fibrillation and loss of surface staining). Proliferation of the synovium on the surface of the ACL and areas of inflammatory cell infiltration was observed within the ACL. Conclusions: We describe the complex enthesis organ of the region posterior to the ACL and show that the intercondylar notch and tibial spines are part of an enthesis organ lined by cartilage. ACL degeneration was observed with increasing tibial plateau width or bigger bones, and increasing height of tibial spines relative to the tibial plateau. Age-related degenerative changes at the ACL have been noted in the absence of cartilage loss, suggesting that microdamage at the ACL could predate cartilage loss in anatomically susceptible individuals. Disclosure of Interest: None declared